Fashion and social status:: a Classic Formula of the White Telephone Films during the Fascist Italy - Tachart, Pajaree (Journal of Letters, 2020)
This article analyses the relationship between fashion, new Italian lifestyle and social mobility that constitute the classic formula of the Italian screwball comedy, the so-called “White Telephone Films”, mainly produced during the second decade of the Fascist period. It focuses on three Italian films directed by Mario Camerini which are Darò un milione (1935), Il Signor Max (1937) and I Grandi Magazzini (1939). Since the mid-1930s, the Government of Benito Mussolini used this genre of Italian cinema as a political tool to manipulate public opinions and to make them accept or even agree with fascist policies. Therefore, the director had to present only beautiful and positive images of the Italian way of life through petite bourgeoisie and working class characters in an idealised society, as it was expected that the simply luxurious life in films would convince and inspire the audience to believe in the values of Fascism and to give consensus to the Fascist Government. The costume designs played an important role in this because they not only represented the characteristics and identities of the characters, coming from different socio-economic backgrounds, but also portrayed how Italian people lived their lives at that time. Moreover, the Italian fashion of the Thirties was integral to the Fascist ideal of the Myth of Italian New Man and Woman and the campaign for Italian Self-sufficiency which contributed to the development of Nationalism before and during the Second World War.